Activation of Protein C and Its Distribution between Its Inhibitors, Protein C Inhibitor, α1-Antitrypsin and α2-Macroglobulin, in Patients with Disseminated intravascular Coagulation - Scully, M F; Toh, C H; Hoogendoorn, H; Manuel, R P; Nesheim, M E; Solymoss, S; Giles, A R (Thrombosis and Haemostasis, 1993)
Activation and inactivation of protein C during the clinical course of disseminated intravascular coagulation (DIC) was studied in three patients by qualitative (Western blotting) and quantitative (ELISA) analysis and the intensity of procoagulant activity monitored by the measurement of thrombin and factor Xa antithrombin III complexes. In one patient, inhibitor complexes of APC with protein C inhibitor (PCI) and α1-antitrypsin (α1-AT) were observed and the latter predominated at presentation. Both disappeared during the development of remission but the loss of α1-AT complexes preceded PCI complexes which on Western blotting appeared to increase in intensity prior to disappearance. The two other patients bled to death from uncontrollable haemorrhage. In both cases, APC/inhibitor complexes with α2-macroglobulin (α2-M) in addition to PCI and αr-AT were detected and persisted until death. Although PCI appeared to be the primary inhibitor in all three cases, α1-antitrypsin and particularly α2-macroglobulin appeared to assume greater roles in the two fatal cases. These data are similar to previous findings in an experimental animal model of DIC that suggested that α2-macroglobulin and α1-antitrypsin become more important inhibitors of APC as the primary inhibitor PCI is consumed in the face of a sustained procoagulant challenge.